Epidemiological studies on measles in children in the District Dera Ismail Khan, Khyber Pakhtunkhwa, Pakistan - Muhammad Ashraf Khan (Microbes and Infectious Diseases, 2025)
Background: Measles is a highly contagious childhood airborne disease caused by a virus. Aged and sex-based monthly prevalence of measles in children aged ≤15 years was determined in the district of Dera Ismail Khan in 2021. Methods: This was a cross-sectional study. The unconsolidated and uncomputerized data was obtained from the admission register of the isolation ward in the Women and Children's Hospital Dera Ismail Khan. Results: Out of the total 1903 measles cases in children, males accounted for 58.8% and females (41.2%). Age group (>1y≤2y) showed 28.1% prevalence of measles, followed by 27.3% (>6m≤1y), 25.7% (>2y≤5y), 9.9% (>5≤10y), 7.6% (≤6 m), and 1.3% (>10y≤15y). April indicated the highest prevalence (20.1%) of measles, followed by March (19.0%), February (14.4%), May (11.5%), January (9.7%), June (5.5%), and December (5.2%). The remaining months showed each ≤3.9% prevalence of the disease. A relatively higher number of measles cases were recorded from February through May, and all age groups showed ≤12.0% relative prevalence in January and during June-December over months. The highest mortality due to the disease occurred in April (15) followed by March (11). Conclusions: The age-wise and month-wise/seasonal-wise variation in the prevalence of measles existed, and showed a peak season of measles is late winter through early summer. Males showed a higher prevalence of disease than females in all months/all age groups except a few cases. The present study helps to design a strategy for the control of measles in the study area.